Pengaruh suplementasi tablet Fe dengan supervisi suami pada ibu hamil terhadap umur kehamilan di Kabupaten Bantul - Dhuto Widagdo; Hamam Hadi; Wiryatun Lestariana (Jurnal Gizi Klinik Indonesia, 2005)
Background: The high prevalence of anemia pregnant women anemia in Indonesia reaches 50%–70%, and it is caused by many factors. First, it may be caused by low compliance of iron supplementation and second, it may be caused by bad distribution of iron supplementation. This prevalence results some effect: high maternal mortality rate, neonatal mortality rate, anemia in infancy, and low productivity. One solution to overcome this prevalence is by giving iron supplementation to pregnant women with husband’s supervision.Objective: This study aims to examine the relationship between iron supplementation with compliance, Hb value, and average of age gestation under husband’s supervision.Methods: This was quasi experimental non-equivalent control group design. Subjects were pregnant women aged 20–28 weeks whose hemoglobin level 8 gr/dl to 15 gr/dl. Subject were taken from three sub-districts of Bantul District, Special Teritory of Yogyakarta. Subject were divided into two groups, the first group (n=55) received 60 mg iron supplementation with husband’s supervision and the second group (n=65) received 60 mg iron supplementation without husband’s supervision.Results: The compliance of first the group was higher than the second group (x2=19,48 p<0,01). In the first group, iron supplementation was effective to increase Hb level it was statistically insignificant (p>0,05). In the second group, iron supplementation was also effective to increase Hb level and it is statistically significant (p<0,05). The difference of Hb level between two groups was insignifi cant. After the predictor variable was controlled using multivariate regression test, it showed that iron supplementation with husband’s supervision was effective to increased Hb level 0,8 gr/dl and statistically signifi cant (p<0,05). The gestation average of two groups was similar, but after predictor variable was controlled using multivariate test, it showed that iron supplementation with husband’s supervision had one week gestation longer than those group without husband’s supervision.Conclusion: Iron supplementation with husband’s supervision are effective to lengthen one week age gestation.